2018
DOI: 10.1371/journal.pone.0209482
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of a brief app-based mindfulness intervention on psychosocial outcomes in healthy adults: A pilot randomised controlled trial

Abstract: BackgroundPrevious evidence suggests that mindfulness training may improve aspects of psychosocial well-being. Whilst mindfulness is traditionally taught in person, consumers are increasingly turning to mindfulness-based smartphone apps as an alternative delivery medium for training. Despite this growing trend, few studies have explored whether mindfulness delivered via a smartphone app can enhance psychosocial well-being within the general public.MethodsThe present pilot randomised controlled trial compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
160
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(171 citation statements)
references
References 63 publications
10
160
0
1
Order By: Relevance
“…The majority of Headspace studies employed samples of university students or residents [ 29 - 35 ], samples of employees [ 36 , 37 ], or clinical samples [ 38 , 39 ]. Only 3 studies of Headspace used community samples, and these participants were predominantly self-selecting, white, well-educated [ 40 , 41 ], and living in Australia [ 40 ] or the United Kingdom [ 42 ]. This contrasts with the sample of this study, which was recruited from a cohort of women representative of the area, of whom 35% were African Americans, only 39% had a college education or higher, and which took place in southern coastal Louisiana, an area that has been subject to quite a few natural and man-made disasters in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of Headspace studies employed samples of university students or residents [ 29 - 35 ], samples of employees [ 36 , 37 ], or clinical samples [ 38 , 39 ]. Only 3 studies of Headspace used community samples, and these participants were predominantly self-selecting, white, well-educated [ 40 , 41 ], and living in Australia [ 40 ] or the United Kingdom [ 42 ]. This contrasts with the sample of this study, which was recruited from a cohort of women representative of the area, of whom 35% were African Americans, only 39% had a college education or higher, and which took place in southern coastal Louisiana, an area that has been subject to quite a few natural and man-made disasters in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with a previous study, which found that participants with higher levels of distress were likely to benefit from application-based mindfulness intervention more than those with a lower level of distress. [ 30 ] However, the findings also put forward the question of whether iMBIs should be remolded to suit specific individuals. A review has reported that mindfulness training with a focus on self-compassion is particularly effective in reducing stress and enhancing professional skills among health care workers who are vulnerable to stress overload and compassion fatigue due to an emotionally exhausting environment.…”
Section: Discussionmentioning
confidence: 99%
“…It is noticeable, however, that only two included studies reported the effect of application-based MBIs on stress. [ 30 , 35 ] Due to the small size of the sample and high heterogeneity across the studies, the findings should be interpreted with caution.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, participants averaged 103 min/week of podcast listening or viewing. Other studies that have tested mobile-app control groups have not reported weekly participation data [ 13 , 26 ]. In our research studies in which we used a commercially available meditation app in college students for 8 weeks [ 15 ] and to patients with MPN cancer for 4 weeks [ 16 ], average weekly participation in meditation on the app was ~38 min/week and ~71 min/week, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Meditation apps have become quite popular in recent years [ 4 , 10 ] and have been used to improve mental and physical health in a range of healthy [ 7 , 11 - 15 ] and health-compromised populations [ 16 , 17 ]. However, few mobile app meditation studies have used active, time-matched, and attention-matched comparators [ 7 , 13 , 14 , 18 ] even when the study primarily aimed to determine effectiveness or efficacy. The most common comparators for these studies have been wait-list control groups, usual care, and educational handouts [ 12 , 15 ].…”
Section: Introductionmentioning
confidence: 99%